Penerapan Terapi Genggam Jari Terhadap Skala Nyeri pada Pasien Post Operasi Appendictomy di RS. PKU Muhammadiyah Karanganyar - Lulu Nabillah Pratiwi; Ika Silvitasari (Yayasan Literasi Sains Indonesia, 2023)
Almost 75% of post-operative surgery patients experience pain complaints. Pain management is a treatment procedure for pain management, which includes both pharmacological and non-pharmacological approaches. Finger graps technique involves graps the fingers of the hand for a relatively short period. The sensation experienced during this technique provides comfort and relaxation, thereby alleviating mental and physical stress, leading to an increase in pain tolerance. To determine the results of implementing finger clenching therapy on the pain scale in patients after appendectomy surgery at PKU Muhammadiyah Hospital in Karanganyar. This research is a descriptive case study with 2 respondents. Based on the observations before applying finger graps therapy using the NRS instrument, Ms. S's pain level was 6 (Moderate Pain), and after the finger graps therapy, the pain scale reduced to 3 (Mild Pain). Meanwhile, Mr. S's pain scale before the finger graps therapy was 5 (Moderate Pain), and after the therapy, the pain scale reduced to 2 (Mild Pain), indicating that finger graps therapy can reduce the pain scale in patients after appendectomy surgery. Finger graps therapy can reduce the pain scale in patients after appendectomy surgery.